2018
DOI: 10.1111/anoc.12088
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Healing Potential of Ibogaine through a Comparative and Interpretive Phenomenology of the Visionary Experience

Abstract: Ibogaine is a hallucinogenic alkaloid, derived from Tabernanthe iboga, a plant unique to the rainforests of West Africa. Its traditional use as an epiphanic sacrament in local magico‐religious practice inspired its appropriation by Western drug addicts by whom it is now hailed as both a catalyst of psychospiritual insight and an effective alleviator of cravings and withdrawal. While scientific and early clinical studies confirm its role in reducing physical withdrawal and craving, debate continues concerning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 66 publications
1
14
0
2
Order By: Relevance
“…In addition, the spectra were normalized to obtain the relative power by dividing the power value of each frequency by the sum across frequencies. The traditional frequency bands depicted in the figures were taken as: delta (1-4 Hz), theta (5-10 Hz), sigma (11)(12)(13)(14), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and gamma (30-100 Hz). Spectral coherence : To measure synchronization between electrodes, we employed the magnitude squared coherence using the mscohere built-in function in Matlab (parameters: window = 1024, noverlap = [], fs = 1024, nfft = 1024), which corresponds to 1-s sliding windows with half-window overlap, and a frequency resolution of 1 Hz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the spectra were normalized to obtain the relative power by dividing the power value of each frequency by the sum across frequencies. The traditional frequency bands depicted in the figures were taken as: delta (1-4 Hz), theta (5-10 Hz), sigma (11)(12)(13)(14), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and gamma (30-100 Hz). Spectral coherence : To measure synchronization between electrodes, we employed the magnitude squared coherence using the mscohere built-in function in Matlab (parameters: window = 1024, noverlap = [], fs = 1024, nfft = 1024), which corresponds to 1-s sliding windows with half-window overlap, and a frequency resolution of 1 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective reports portray the ibogaine experience as entering into an intense dream-like episode while awake, involving memory retrieval and prospective imagination, without producing the typical interferences in thinking, identity distortions, and space-time alterations produced by classical psychedelics (e.g. DMT, LSD, psilocybin) [8][9][10][11][12][13][14] . Thus, ibogaine is often referred as an oneirogenic psychedelic 8,10,15 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the spectra were normalized to obtain the relative power by dividing the power value of each frequency by the sum across frequencies. The traditional frequency bands depicted in the figures were taken as: delta (1-4 Hz), theta (5-10 Hz), sigma (11)(12)(13)(14), beta (15-29 Hz) and gamma (30-100 Hz).…”
Section: Discussionmentioning
confidence: 99%
“…Under the influence of ibogaine, rats demonstrated rapid acquisition of spatial memory. Rodger (2018) suggested that the experience of retrieving childhood memories and the creation-migration mythology experienced by the Bwiti are regressions. These regressions can be childhood memories, traumatic events or social dynamics that played a role in shaping the perceptions of the individual.…”
Section: The Psychological Aspects Of Ibogainementioning
confidence: 99%